Differential impact of abluminal groove‐filled biodegradable‐polymer sirolimus‐eluting stent versus durable‐polymer everolimus‐eluting stent on and off dual antiplatelet therapy. Issue 2 (27th January 2021) - Saito, Yuichi; Wijns, William; Baumbach, Andreas; Xu, Bo; Kelbæk, Henning; Zheng, Ming; Morel, Marie‐angèle; Anderson, Richard; Schächinger, Volker; Lansky, Alexandra; ,
Abstract: Background: Current guidelines recommend dual antiplatelet therapy (DAPT) following percutaneous coronary intervention for 6–12 months in patients with acute coronary syndrome (ACS) and 3–6 months in those with chronic coronary syndromes (CCS). Whether DAPT duration has a differential effect on outcomes following treatment of ischemic coronary disease with durable versus biodegradable drug‐eluting stent (DES) is poorly defined. Methods: The TARGET All Comer study was a randomized trial of patients with ischemic coronary artery disease assigned to treatment with either a biodegradable polymer DES (Firehawk) or a durable polymer DES (XIENCE). This pre‐specified TARGET AC sub‐analysis sought to evaluate the 2‐year clinical outcomes before and after DAPT discontinuation. The primary endpoint was target lesion failure (TLF). Results: A total of 1, 296 (78.4%) of 1, 653 randomized patients were included in this substudy, of which 1, 210 (93.4%) remained on DAPT at 6 months, 863 (66.6%) at 12 months, and 409 (31.6%) at 2 years. There was no difference in TLF between patients treated with Firehawk and XIENCE stents from index procedure to DAPT discontinuation (8.0 and 7.7%, p  > .99) or after DAPT discontinuation (2.9 vs. 3.8%, p = .16). After DAPT discontinuation, target vessel myocardial infarction (1.3 vs. 3.3%, p = .07), and ischemia‐driven target lesion revascularization (0.5 vs. 1.9%, p = .06) favored treatment with Firehawk. Conclusions: Although TLF was comparable for both Firehawk and XIENCE stent groups before and after DAPT discontinuation, after DAPT discontinuation, there was a trend for less target vessel myocardial infarction and ischemia‐driven revascularization with the biodegradable polymer DES.